Glutamatergic transmission in drug reward: implications for drug addiction - D'Souza, Manoranjan S. (Frontiers in Neuroscience, 2015)
Individuals addicted to drugs of abuse such as alcohol, nicotine, cocaine, and heroin are a significant burden on healthcare systems all over the world. The positive reinforcing (rewarding) effects of the above mentioned drugs play a major role in the initiation and maintenance of the drug-taking habit. Thus, understanding the neurochemical mechanisms underlying the reinforcing effects of drugs of abuse is critical to reducing the burden of drug addiction in society. Over the last two decades, there has been an increasing focus on the role of the excitatory neurotransmitter glutamate in drug addiction. In this review, pharmacological and genetic evidence supporting the role of glutamate in mediating the rewarding effects of the above described drugs of abuse will be discussed. Further, the review will discuss the role of glutamate transmission in two complex heterogeneous brain regions, namely the nucleus accumbens (NAcc) and the ventral tegmental area (VTA), which mediate the rewarding effects of drugs of abuse. In addition, several medications approved by the Food and Drug Administration that act by blocking glutamate transmission will be discussed in the context of drug reward. Finally, this review will discuss future studies needed to address currently unanswered gaps in knowledge, which will further elucidate the role of glutamate in the rewarding effects of drugs of abuse.